Semisynthesis of Andrographolide Derivatives and Evaluation of Their Antitumour Properties - Rao, Jada Srinivasa (2004)
Previously, andrographolide, which is the major diterpenoid of Andrographis paniculata, was shown to have in vivo antitumour activity against human breast tumour xenografts. In this study, among the four compounds isolated from A. paniculata, andrographolide was the most potent compound with a mean ICso value of 8 IlM in MCF-7 human breast cancer cells. Neoandrographolide showed a weak cytotoxic effect, whereas 14-deoxy-ll, 12-didehydroandrographolide and 14-deoxyandrographolide failed to exhibit growth inhibitory effect at the highest tested concentration of 100 uM. Owing to this, andrographolide was considered as the lead compound in the discovery of potent and selective antitumour agents. Using andrographolide isolated from A. paniculata as one of the starting materials, 3,19-benzylidene andrographolide and 3,19-alkylidene andrographolide derivatives were synthesised by coupling of the two -OH groups present at C-3 and C-19 of andrographolide with different benzaldehydes and alkyl aldehydes, respectively. In addition, new derivatives were also synthesised by acetylation, oxidation, Heck and esterolysis reactions. The structures of new derivatives of andrographolide derivatives were confirmed by spectral analysis eH/J3C NMR, MS, FT-IR, UV).Forty seven compounds including andrographolide were tested for antitumour activities in MCF-7 and HCT-116 (colon) cancer cell lines. Using a 72 h MTT cell viability assay, parameters of dose-response effects, GIso, TGI and LCso were determined. The derivatives had submicromolar GIso values, except for 3,19-(4nitrobenzylidene) andrographolide (SRJS8), which showed the most potent activity with a GIso value of 0.7 uM in MCF-7 cells. Only (Z)-2-[1-benzylamino-2-(5,5,6,8atetramethyl- 2-methylene-decahydro-naphthalen-1-yl)-ethyl]-4-hydroxy-but-2-enoic acid benzylamide] (SRJ18), displayed a pronounced selectivity (approximately 8-fold) towards HCT-116 cells at the GIso value compared with MCF-7 cells.Out of the five compounds (3,19-isopropylideneandrographolide (SRJOl), 14acetylandrographolide (SRJ03), 3,19-(2-bromobenzylidene)-14-deoxy-11, 12-didehydro andrographolide (SRJOS), 3,19-(2-bromobenzylidene)andrographolide (SRJ09) and 3,19-(3,4-dimethoxybenzylidene)andrographolide (SRJ13)) tested against the 60 National Cancer Institute (NCI) of USA human cancer cell lines, only SRJ09 showed some form of selectivity towards cancers of the colon, central nervous system, renal and melanoma.The mechanism(s) of actions of the compounds were also studied by determining their effect in inducing cell cycle arrest and apoptosis. Andrographolide, SRJOI and SRJ03 induced G1 and Gz/M arrest in MCF-7 cells, whereas 3,19-(4bromobenzylidene) andrographolide (SRJ08), SRJ09, 3,19-(3-bromobenzylidene) andrographolide (SRJIO), 3,19-(3-chloro-4-fluorobenzylidene)andrographolide (SRJ23) and 3,19-(2-fluorobenzylidene)andrographolide (SRJ27) induced only GI-phase arrest in MCF-7 cells. SRJ09 down-regulated CDK4 (a G]-phase regulator) protein levels in MCF-7 cells, which explains the G] -phase arrest by the compound. NCrs COMPARE mechanistic analysis revealed that the compounds antitumour activities were not similar to that of standard anticancer drugs with known mechanisms of action. Projection of SRJ03 in the Self-Organising Maps (SOMs) analyses of NCr suggested that this compound may be targeting cell cycle related phosphatases or kinases. However, andrographolide, SRJOl, SRJOS, SRJ09 and SRJ13 did not project in the known mechanism categories. The mode(s) of cell death induced by SRJ09 and SRJ23, identified by fluorescence microscopy and flow cytometry, was confirmed to be apoptosis in HCT-116 cells. In conclusion, novel derivatives of andrographolide, especially SRJ09, SRJ18 and SRJS8 are potential lead molecules for future antitumour studies to discover prospective clinical candidates.